2008
DOI: 10.1071/wr07023
|View full text |Cite
|
Sign up to set email alerts
|

Indexing small mammalian carnivores in the southern Kalahari, South Africa

Abstract: Monitoring animal populations in changing environments is crucial to wildlife conservation and management, but restrictions in resources are a recurring problem for wildlife managers and researchers throughout Africa. Land-useinduced shrub encroachment in Kalahari savannah rangelands has led to fragmentation of the landscape. Mammalian carnivores are particularly vulnerable to local extinction in fragmented landscapes, but their low numbers and their often nocturnal and secretive habits make them difficult to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Binary data were only weakly or even negatively correlated with trap results (Table 1). This latter result was not entirely unexpected, since the reduction of continuous data to binary data represents a loss of information (Allen A. et al, 1996, Allen B. et al, 2011Baldwin et al, 2014;Blaum et al, 2008;Engeman, 2005;Engeman et al, 1989).…”
Section: Initial Trialmentioning
confidence: 99%
“…Binary data were only weakly or even negatively correlated with trap results (Table 1). This latter result was not entirely unexpected, since the reduction of continuous data to binary data represents a loss of information (Allen A. et al, 1996, Allen B. et al, 2011Baldwin et al, 2014;Blaum et al, 2008;Engeman, 2005;Engeman et al, 1989).…”
Section: Initial Trialmentioning
confidence: 99%
“…For example, tracking plots are easier to record as showing activity or not, without accurately recording the intensity of activity at each station. Nevertheless, reduction of potentially continuous data to binary observations is easily demonstrated to have less descriptive ability and result in a greater opportunity for erroneous inferences (Engeman et al 1989), and this principle has been especially well-demonstrated for tracking plot data (e.g., Allen et al 1996Allen et al , 2011Blaum et al 2008;Engeman 2005;Engeman et al , 2002.…”
Section: Measurementsmentioning
confidence: 99%
“…Engeman and Evangelista, 2006;Blaum et al, 2008;Claridge et al, 2010). Almost all studies addressing the ecological roles of dingoes in Australian ecosystems have used this fauna sampling technique (Allen et al, 2013b), for which a great deal of methodological development and validation has been undertaken (Engeman et al, 1998;Engeman, 2005;Allen and Engeman, 2014).…”
Section: Passive Tracking Indicesmentioning
confidence: 99%